Indonesian EFL Pre-service Teachers' Experiences: Revealing English Instructional Challenges during Teaching Practice - Abdillah, Muhammad Ghozali; Fithriani, Rahmah (REiLA : Journal of Research and Innovation in Language, 2023)
EFL pre-service teachers who desire to become qualified must practice teaching in school settings to apply classroom-learned skills. Consequently, adequate preparation at the numerous schools and their readiness where they would teach is essential. This qualitative research investigates the challenges Indonesian EFL pre-service teachers encounter in English instruction during teaching practice. This study utilized a phenomenological case study approach, as it offers significant benefits in comprehending the intricate dynamics involved in becoming an English teacher. To ensure impartiality and fairness in the research, a purposive sampling technique was employed to select 10 out of 40 pre-service teachers as critical informants who could provide valuable insights into the subject matter and facilitate the identification of information-rich cases. The collection of data was conducted through the utilization of semi-structured interviews, teaching diaries, and teaching videos. The findings indicate that EFL pre-service teachers encounter challenges in effectively communicating instructions, which can be attributed to various factors such as insufficient resources, limited access to media, inadequate preparation, disruptive behavior of learners, and insufficient proficiency in English and pedagogical knowledge. Nevertheless, this study has identified three significant challenges: inadequacy of teaching resources, the absence of respect, and insufficient content knowledge. The findings suggest that school administrators, policymakers, and other stakeholders must develop productive, systematic, and structured induction experiences for novice teachers, particularly those still in the process of completing their teacher training, to address the challenges they encounter.